Effects of Methane-Rich Saline on the Capability of One-Time Exhaustive Exercise in Male SD Rats. - Lei Xin; Xuejun Sun; Shujie Lou (PLoS ONE)
Purpose To explore the effects of methane-rich saline (CH4 saline) on the capability of one-time exhaustive exercise in male SD rats. Methods Thirty rats were equally divided into to three groups at random: control group (C), placebo group (P) and methane saline group (M). Rats in M group underwent intraperitoneal injection of CH4 saline, and the other two groups simultaneously underwent intraperitoneal injection of normal saline. Then, the exercise capability of rats was tested through one-time exhaustive treadmill exercise except C group. Exercise time and body weight were recorded before and after one-time exhaustive exercise. After exhaustive exercise, the blood and gastrocnemius samples were collected from all rats to detect biochemical parameters in different methods. Results It was found that the treadmill running time was significantly longer in rats treated with CH4 saline. At the same time, CH4 saline reduced the elevation of LD and UN in blood caused by one-time exhaustive exercise. The low level of blood glucose induced by exhaustive exercise was also normalized by CH4 saline. Also CH4 saline lowered the level of CK in plasma. Furthermore, this research indicated that CH4 saline markedly increased the volume of T-AOC in plasma and alleviated the peak of TNF-α in both plasma and gastrocnemius. From H&E staining, CH4 saline effectively improved exercise-induced structural damage in gastrocnemius. Conclusions CH4 saline could enhance exercise capacity in male SD rats through increase of glucose aerobic oxidation, improvement of metabolic clearance and decrease of exhaustive exercise-induced gastrocnemius injury.